Inventory and documenting scalable innovations in WEFE nexus context in the Aral Sea region - Djumaboev, Kakhramon; Akramkhanov, Akmal (International Center for Agricultural Research in the Dry Areas, 2023)
This report provides information about inventory and documenting scalable innovations in WEFE nexus content in the Aral Sea region.